EXPRESSION OF PRISONERS AS A FORM OF ANXIETY DURING PRISON: A PSYCOPRAGMATIC STUDY (EKSPRESI NARAPIDANA SEBAGAI BENTUK KECEMASAN SELAMA DI PENJARA: STUDI PSIKOPRAGMATIK) - Rani Setiawaty; Harun Joko Prayitno; Atiqa Sabardila; Markhamah Markhamah; Tri Santoso (Universitas PGRI Sumatera Barat, 2021)
Overcapacity in prisons and non maximized empowerment activities can affect the psychological prisoners such as stress, boredom, or anxiety. Autobiographical expressive writing is used as a way to express regret, sadness, distress, stress, boredom, anxiety, and hone their potential. The research aims: (1) to identify the use of prisoners’ expressive perlocotion; and (2) to uncover prisoners’ problems in Rutan class I A Surakarta. The research type is descriptive-qualitative using a psycho pragmatic approach. Data sources are autobiographical texts write by prisoners in Rutan Class IA Surakarta from a variety of cases and diverse educational backgrounds. Data analysis methods are translasional identity (the determining tool is language/speech), referential identity (the determining tool is something outside the language or problems faced by prisoners and ESA types), and pragmatic identity (the determining tool is the interlocutor). Based on the results and discussion concluded that (1) the speech act of expressive perlocotion in prisoners’ autobiography in Rutan Class I A Surakarta consists of regret, hope, recognition, complaining, pride, sadness, happiness, regret, suggest, criticize, resentment, disappointment, confidence, possibility, gratitude, and praise. (2) The problems disclosed by the prisoners relate to personal, social, economic, and legal issue.